Methodology of the remote audit efficiency - L. N. Lebedinskaya; N. K. Rozhkova; D. Yu. Rozhkova (Вестник университета, 2022)
Remote audit is performed using information and communication technologies to collect, store, retrieve, process, analyse and transmit information. Before the COVID-19 pandemic, remote audits were carried out on a relatively small scale (for example, checking enterprises with hazardous production) or in case of unforeseen circumstances. During the COVID-19 pandemic, businesses, regulators and households have been forced to switch to work remotely, based on existing and developing new technologies. This article analyses remote audits and their effectiveness. To do this, autors have been conducted 18 interviews with representatives of the audit profession (leading auditors, auditors) and audit clients. The result has been the identification of the main differences between the process of traditional and remote audit, difficulties and features. Based on existing methods for analysing the audits’ effectiveness, and using a balanced scorecard, we have developed a methodology for assessing the effectiveness of remote audits (including indicators that affect the effectiveness of only remote audits).